Influences of Cocoa Polyphenols and Enzyme Reactivation on the Flavor Development of Unfermented and Under-Fermented Cocoa Beans - Misnawi, . (2003)
Polyphenols are mainly responsible for the formation of astringency and bitterness in cocoa beans. Due to the propensity of polyphenols to interact with other compounds, studies have been carried out to evaluate influences of polyphenols in the development of cocoa flavor. The studies started with the evaluation of polyphenol changes during cocoa fermentation and roasting, followed by the study on the development of flavor during roasting of cocoa liquor at different polyphenol concentrations. In order to overcome the low aroma and excessive astringency problems in unfermented and under-fermented cocoa beans, studies on the reactivation of the remaining key enzymes in these beans were also carried out. The study found that polyphenol concentration was reduced as high as 53% during cocoa fermentation. Oxidation and derivatization of the cocoa polyphenols decreased polyphenol ability to interact with protein and produce astringency as supported by the decrease in tannin concentration as high as 39% from the concentration prior to fermentation and decrease in more hydrophobic polyphenols proportion during cocoa fermentation. Monomers, trimers and tetramers at 36, 20 and 16%, respectively were the predominant polyphenols present in unfermented cocoa bean. However, in fermented cocoa bean they were monomers, dimers and trimers which were 29, 16 and 16% of the total polyphenol, respectively. Pentamers, tetramers and dimers were highly correlated (p<0.01) with astringency and bitterness. Roasting of cocoa liquor at 120°C for 15 to 45 min significantly (p<0.05) reduced polyphenol hydrophobicity and concentrations of polyphenol and tannin. During the roasting process, concentrations of polyphenol and tannin in fermented cocoa liquor decreased 2.6-3.3% and 20-33% from the concentration prior to roasting, respectively. However, in the fermented cocoa liquor enriched with unfermented cocoa polyphenol at 170 g kg-l, the decreases were 4.7-8.9% and 2.3-7.5%, respectively. Increases in polyphenol concentration in cocoa liquor from 58 to 170 g kg-l did not only produce excessive astringency and bitterness, but also caused reduction on pyrazine formation during roasting. The reduction on the formations of 2,3,5-trimethyl- and 2,3,5,6-tetramethy- occurred through out roasting period. However, the reduction against 2,5-dimethyl- only occurred at 35 min roasting time. Reduction on the formation of 2,3-dimethylpyrazine occurred at 25, 35 and 45 min roasting time. Sensory evaluation indicated that the increases in polyphenol concentration significantly (p<0.05) lowered the cocoa flavor and viscosity, and increased astringency and bitterness; however, it did not influence acidity, fruity/floral/bouquet, raw/green, smoky and mouldy/earthy properties of the liquor. Cocoa flavor scored at 6.4 out of maximum score of 10 was decreased to 5.2 due to the polyphenol increases from 58 to 170 g kg-1. However, viscosity score was decreased from 4.2 to 3.0. In contrary, astringency score was increased from 3.6 to 5.3, and bitterness score was increased from 3.2 to 4.9. Key enzymes remained in dried unfermented cocoa bean, namely polyphenol oxidase, aspartic endoprotease, carboxypetidase and invertase bean were found at 1, 33, 20 and 19% from the original activities, respectively; however, those in under-fermented cocoa bean were 0.08, 31, 16 and 7%, respectively. Reactivation of these enzymes through incubation at 45°C, pH 3.5-6.5 reduced the excessive polyphenol concentration and produced aroma precursors in the dried cocoa beans. Crude polyphenol oxidase extracted from fresh freeze-dried unfermented cocoa bean and tyrosinase from mushroom at concentration of 88-8,800 U g-I could also be used to enhance oxidation of cocoa bean polyphenols.